The Assyrian Genocide: Cultural and Political Legacies - Travis, Hannibal (Routledge Studies in Modern History, 2017)
Cover -- Title -- Copyright -- Dedication -- Contents -- List of figures and tables -- List of contributors -- Acknowledgements -- Glossary -- List of judicial decisions cited -- Table of legislation -- 1 The Assyrian genocide across history: collective memory, legal theory, and power politics -- 2 The term Seyfo in historical perspective -- 3 The atrocities against the Assyrians in 1915: a legal perspective -- 4 The Ottoman genocide of the Assyrians in Persia -- 5 Abduction, rape, and genocide: Urmia's Assyrian girls and women -- 6 Genocide/ Seyfo - and how resistance became a way of life -- 7 Lady Surma: the pillar of the Assyrian nation, 1883-1975 -- 8 The Assyrian delegation at the Paris Peace Conference -- 9 The Assyrian "concept of unity" after Seyfo -- 10 Exile or extinction: the Assyrian genocide from 1915 to 2015 -- 11 Epilogue: tombstones and inverted crosses -- Index